Comparison Of Handicap Inventory Tinnitus Scores Before and After Intra Tympanic Steroid Injection In Tinnitus Patients - Amir Hamzah; Erial Bahar; Ahmad Hifni; Abla Ghanie (Biomedical Journal of Indonesia, 2022)
Introduction. Tinnitus is a symptom in the form of a conscious perception of sound that is not produced by a sound source outside the body. Patients with tinnitus often have complaints of quality of life, with some situations of extreme anxiety, depression, and life changes. The Tinnitus Handicap Inventory (THI) is a valid questionnaire to be associated with patients associated with tinnitus. The Tinnitus Research Initiative (TRI), an international academic organization founded in 2006, recommends the use of THI for the evaluation of tinnitus defects and therapeutic effects. Therefore, a THI assessment is needed at RSUP Dr. Mohammad Hoesin Palembang as a result of therapy. Methods. This research using a design that aims to determine the comparison of THI scores before and after intratympanic injection of corticosteroids in 18 samples at RSUP Dr. Mohammad Hoesin Palembang. Results. The average age of the sample was 57 (23-66) years and the number of men and women were the same, namely 9 (50%) samples. Most of the samples had problems in unilateral ears by 14 (77,8%) samples. The average THI before intratympanic steroid injection was 37 (12-72) and after injection was 20 (4-80). Wilcoxon test results showed significant changes between before and after intratympanic steroid injection. Conclusion. There was a significant improvement in THI scores after intratympanic steroid injection.